2021
DOI: 10.3390/cancers13153805
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethality Screening Highlights Colorectal Cancer Vulnerability to Concomitant Blockade of NEDD8 and EGFR Pathways

Abstract: Colorectal cancer (CRC) is a heterogeneous disease showing significant variability in clinical aggressiveness. Primary and acquired resistance limits the efficacy of available treatments, and identification of effective drug combinations is needed to further improve patients’ outcomes. We previously found that the NEDD8-activating enzyme inhibitor pevonedistat induced tumor stabilization in preclinical models of poorly differentiated, clinically aggressive CRC resistant to available therapies. To identify drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“… 435 In BRAF-mutant and RAS/RAF wild-type CRC cells, double blocking of NEDD8 and EGFR pathways led to cell growth arrest and increased apoptosis induction. 436 Sun et al reported the novel synthetic lethal partners, Src and PARP1, that exerted a pronounced anticancer effect on HCC cells and could suppress the resistance to PARP1 inhibition. 437 Moreover, a combination of sorafenib and selumetinib was also an effective therapy in HCC cells having high p-ERK levels.…”
Section: Combination Therapy Of Targeted Small-molecule Compounds In ...mentioning
confidence: 99%
“… 435 In BRAF-mutant and RAS/RAF wild-type CRC cells, double blocking of NEDD8 and EGFR pathways led to cell growth arrest and increased apoptosis induction. 436 Sun et al reported the novel synthetic lethal partners, Src and PARP1, that exerted a pronounced anticancer effect on HCC cells and could suppress the resistance to PARP1 inhibition. 437 Moreover, a combination of sorafenib and selumetinib was also an effective therapy in HCC cells having high p-ERK levels.…”
Section: Combination Therapy Of Targeted Small-molecule Compounds In ...mentioning
confidence: 99%
“…Examples include combination of bortezomib with vorinostat and dexamethasone in relapsed multiple myeloma [NCT01720875 ( 34 )]. Pevonedistat was found to synergize with EGFR pathway inhibition, leading to tumor regression, in CRC xenograft models ( 35 ). Bortezomib and pevonedistat could also increase the efficacy of immunotherapy, because both drugs have been shown to induce immunogenic cell death, potentially enhancing antitumor immunity and allowing more durable responses to immunotherapy ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may also participate in tumorigenesis, growth and metastasis by regulating multiple signaling pathways. There is a strong association between NEDD8 overactivation and cancer progression in lung cancer, breast cancer (51), liver cancer (71) and colorectal cancer (72). NEDD8-mediated upregulation of neddylation has been found in lung cancer, affecting the prognosis and treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…NEDD8-mediated neddylation is closely related to the occurrence and development of tumors. Overexpression of neddylation-related proteins has been seen in lung cancer (30), breast cancer (51), liver cancer (71) and colorectal cancer (72) and may significantly reduce the overall survival rate of patients. To date, it has been found that the expression pattern of NEDD8-related proteins has changed in cancerous lung tissues, including large-cell neuroendocrine carcinoma of the lung (LCNEC), lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) (73).…”
Section: Effects Of Neddylation On Lung Cancermentioning
confidence: 99%